Effect of composts on microbial dynamics and activity, dry root rot severity and seed yield of cowpea in the Indian arid region - BAREJA, Meenu; KUMAR, Praveen-; LODHA, satish (Phytopathologia Mediterranea, 2011)
Nutrient-deficient sandy soil, having poor moisture retention, favors Macrophomina phaseolina, a soil-borne plant pathogen, occurring in severe form on many important crops grown in the Indian arid region. In a 2-year field experiment, five composts (4 ton/ha) prepared from residues of Calotropis procera, Prosopis juliflora, Azadirachta indica, Acacia nilotica, and on-farm weeds were tested on cowpea (Vigna unguiculata) to determine their effectiveness in limiting the severity of charcoal rot caused by M. phaseolina in relation to the microbial population dynamics, microbial activity and the seed yield of cowpea. In general, compost-amended plots retained 8.9% higher moisture than unamended plots. The microbial population increased in amended plots during the crop season. Populations of total fungi and actinomycetes were heighest in Calotropis compost-amended soil, while total bacteria were maximum in weed- compost amended soil. Microbial activity in amended plots was 26.3% higher than in unamended plots. Among trace elements, uptake of Zn, Mn, Fe and Cu was heighest in plants grown in weed-compost amended soil followed by A. nilotica compost-amended soil. Soil amendment with the composts significantly reduced plant mortality due to charcoal rot. The lowest mortality was recorded in plants amended with A. nilotica compost (5.5%) followed by P. juliflora compost (5.8), while the highest plant mortality (11.5%) from charcoal rot occurred in the unamended control on the basis of the pooled average of two years. There was a significant inverse correlation between microbial activity and charcoal rot incidence in cowpea at 20 days after planting. Composts also had a beneficial effect on yield, with a 28.3% increase in seed yield in P. juliflora compost-amended plots. These results suggest that in resource-deficient farming , certain on-farm wastes can be effectively utilized for managing soil-borne pathogens, as well as for enhancing crop productivity.